Applying research to enhance capacity: A unifying purpose for an integrated profession - Keenan, Elizabeth King (Journal of Social Work Education, 2016)
For more than a century the social work profession has had a dual purpose: to promote individual well-being and social justice, but the micro-macro divide is fragmenting the profession. This article suggests that the profession's aim might best be realized by adopting a unifying purpose, a just sense of well-being. Research on complex adaptive systems conceptualizes a unifying purpose as vertical integration carried out in differentiated ways in discrete moments of practice in various settings. Interpersonal neurobiology and Aristotle's interdependence of character virtues and practical judgment inform a corresponding shift from the dualities of personal and professional to the social worker as a person with differentiated professional capacities and activities. Integration with differentiation enhances capacity to promote the profession's purpose.
1 citations (Crossref) [2023-10-31] tex.eissn: 2163-5811 tex.unique-id: ISI:000381004400007
Keywords: dept.swk; differentiation; human; human experiment; morality; neurobiology; occupation; peer-reviewed; social justice; social work; wellbeing